Kebijakan Bea Masuk Impor Barang E-commerce Dalam Kaitannya Dengan Hukum Persaingan Usaha - Adelia Rizky Windyaka (Jurist-Diction, 2021)
AbstractThe government made Law Number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition to regulate business actors in carrying out activities related to buying and selling in the market. The birth of this regulation provides a limit for business actors to create healthy business competition. The presence of a platform for online shopping also makes trading activities easier today. The development of this shopping style also affects the number of imported goods that enter Indonesia. There is a policy regarding the setting of the value for import duties on imported goods which has increased from the previous one. The change in the value of this import duty is a step by the government to protect domestic business actors.Keywords: Law; Bussiness competition; Policy; Import.AbstrakPemerintah membuat Undang – Undang Nomor 5 tahun 1999 tentang larangan praktek monopoli dan persaingan usaha tidak sehat untuk mengatur pelaku usaha dalam melakukan kegiatan yang berkaitan dengan jual beli didalam pasar. Lahirnya peraturan ini memberikan batasan bagi pelaku usaha agar menciptakan persaingan usaha yang sehat. Hadirnya platform untuk berbelanja online juga mempermudah kegiatan perdagangan saat ini. Berkembangnya gaya berbelanja ini juga berpengaruh terhadap banyaknya barang impor yang masuk ke Indonesia. Terdapat kebijakan mengenai pengaturan besaran nilai bagi bea masuk barang impor yang mengalami kenaikan dari sebelumnya. Berubahnya nilai bea masuk ini sebagai langkah pemerintah melindungi pelaku usaha domestik.Kata Kunci: Hukum; Persaingan Usaha; Kebijakan; Impor.